2013
DOI: 10.1038/cddis.2012.214
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells rescue implantation defects caused by c-kit deficiency

Abstract: Various physiologically relevant processes are regulated by the interaction of the receptor tyrosine kinase (c-Kit) and its ligand stem cell factor (SCF), with SCF known to be the most important growth factor for mast cells (MCs). In spite of their traditional role in allergic disorders and innate immunity, MCs have lately emerged as versatile modulators of a variety of physiologic and pathologic processes. Here we show that MCs are critical for pregnancy success. Uterine MCs presented a unique phenotype, accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
131
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(150 citation statements)
references
References 51 publications
9
131
2
2
Order By: Relevance
“…Gal-1 secreted by MCs positively influences spiral artery formation and thus placentation, which finally allows the normal growth and development of the fetus within the uterus. 58 Another molecule influencing pregnancy at various checkpoints is the heme-degrading enzyme heme oxygenase-1 (HO-1). HO-1-deficient females were initially reported as sterile after observing that no progeny could be obtained after mating Hmox1 À/À females with Hmox1 À/À males.…”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 99%
“…Gal-1 secreted by MCs positively influences spiral artery formation and thus placentation, which finally allows the normal growth and development of the fetus within the uterus. 58 Another molecule influencing pregnancy at various checkpoints is the heme-degrading enzyme heme oxygenase-1 (HO-1). HO-1-deficient females were initially reported as sterile after observing that no progeny could be obtained after mating Hmox1 À/À females with Hmox1 À/À males.…”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 99%
“…Not only do they contribute to innate and adaptive immune responses (Galli et al 2005, St John & Abraham 2013, but also they are directly involved in non-immunological processes including tissue remodeling and angiogenesis (Varayoud et al 2004, Bosquiazzo et al 2007, Theoharides et al 2010. Their effects are mainly mediated by granule-stored mediators such as metalloproteases, MC-specific proteases, tissue plasminogen activator (tPA), vascular endothelial growth factor (VEGF), transforming growth factor b (TGFb) (Galli et al 2005) and galectin 1 (Gal1, Woidacki et al 2013) that are released upon activation. We have recently reported that MCs migrate from the periphery to the uterus responding to hormonal fluctuations (Jensen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model, Kit (c-Kit) deficiency, which is associated with a lack of MCs including uterine MCs (uMCs), was related to impaired implantation and placentation that negatively influenced fetal growth (Woidacki et al 2013). We found these effects to be mediated by Gal1 as bone marrow-derived MCs (BMMCs) from WT mice but not from Lgals1 (Gal1)-deficient mice could rescue the impaired reproductive phenotype (Woidacki et al 2013). The in vivo behavior of MCs at the fetal-maternal interface is, however, largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations